PENGGUNAAN MEDIA FLASHCARD TERHADAP HASIL BELAJAR IPA SISWA SEKOLAH DASAR - Alvan Hazhari; Maya SIh Hika Pamungkas; Yetty Kurniawati (Journal of Professional Elementary Education, 2023)
The problem of science learning outcomes that occur there are students who are less active/focused on learning material, difficulty memorizing material, students do not have strong motivation and interest, students feel bored in teaching and learning activities, lack of skill in using media in the learning process. so that the ability of science learning outcomes does not reach the KKM. The purpose of this study was to determine the use of Flashcard media on the science learning outcomes of elementary school students. The research method used is library research (literature study) from 10 journals and theses as primary library sources and 7 books as secondary libraries, the using Flashcard media on student science learning outcomes with intervals of the last ten years starting from 2012-2021. The results showed that the type of media used for students' science learning outcomes was Flashcard media that every research that had been carried out obtained percentage results that showed an increase in student learning outcomes, from the results of research conducted by previous researchers that the use of Flashcard media can improve learning outcomes. student science. The conclusion of this study is that there are positive results in learning in the use of Flashcard media on science learning outcomes